(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Preservatives are substances added into product to prevent their premature spoilage. Preservative helps to prolong the product’s shelf life by protecting the product from microbial growth and oxidation process. In this study, the potential of a Piper sp. as preservative for cosmetic products is being investigated. The exploration begins with the screening of major phytochemical groups; flavonoid, steroid, alkaloid, saponin and triterpene. Evaluation of biological activities exhibited the plant possessed antimicrobial property towards two strains of Staphylococcus aureus and free radical scavenging capacity. The minimum inhibitory concentration values (MIC) for both S. aureus ATCC 25923 and S. aureus ATCC 6538 is 2500 mg/mL and 312.5 mg/mL respectively. Free radical scavenging capacity of the plant was determined via Superoxide scavenging assay and DPPH radical scavenging assay and the capacity values are 76.4+0.35% and 59.7+0.75% respectively. Cytotoxicity study was also carried out to determine the safety of Piper sp. where median inhibitory concentration (IC50) value for normal kidney cell lines (Vero) is 62.96 mg/mL and normal liver cell lines (WRL-68) is 69.91mg/mL. The extract of Piper sp. was formulated as cosmetic preservative ingredient especially for topical product. The specification of ingredient’s characteristic and performance were described based on colour, odour, pH value as well the solubility in product formulation and stability at 4°C, room temperature and 40°C.